Review on the occurrence and biological effects of illicit drugs in aquatic ecosystems - Fontes, Mayana Karoline [UNESP]; Maranho, Luciane Alves [UNESP]; Pereira, Camilo Dias Seabra (Springer, 2020)
Illicit drugs (IDs) and their metabolites are recognized as contaminants of emerging concern. After consumption, illicit drugs are partially metabolized and excreted unchanged in urine and feces or as active metabolites reaching wastewater treatment plants (WWTPs). Furthermore, most WWTPs are insufficient in the treatment of effluents containing IDs, which may be released into aquatic ecosystems. Once in the water or sediment, these substances may interact and affect non-target organisms and some evidences suggest that illicit drugs may exhibit pseudo-persistence because of a continuous environmental input, resulting in long-term exposure to aquatic organisms that may be negatively affected by these biologically active compounds. We reviewed the literature on origin and consumption, human metabolism after consumption, aquatic occurrences, and toxicity of the major groups of illicit drugs (opioids, cannabis, synthetic drugs, and cocaine). As a result, it could be concluded that illicit drugs and their metabolites are widespread in diverse aquatic ecosystems in levels able to trigger sublethal effects to non-target organisms, besides to concentrate in seafood. This class of emerging contaminants represents a new environmental concern to academics, managers, and policymakers, whose would be able to assess risks and identify proper responses to reduce environmental impacts.
Keywords: Illicit drugs; Aquatic ecosystems; Non-target organisms; Emerging contaminants